RSA-AES Cryptosystem with Auto-Key Rotation for Cloud Storage - Azanuddin Azanuddin; Asyahri Hadi Nasyuha; Ikhwan Ruslianto; Moch. Iswan Perangin Angin; Moustafa H. Aly; Moses Adeolu Agoi (UIN Sumatera Utara, 2025)
The widespread adoption of cloud storage systems has increased the demand for cryptographic mechanisms that ensure data confidentiality while limiting security risks associated with static and long-lived encryption keys. Although hybrid RSA-AES schemes are commonly employed to balance security and computational efficiency, key management-particularly autonomous and quantitatively bounded key rotation-remains insufficiently formalized. This study proposes a hybrid RSA-AES cryptosystem equipped with an autonomous auto-key rotation mechanism defined through explicit analytical constraints. AES-256 is employed for bulk data encryption, while RSA-2048 is used for secure encapsulation of symmetric session keys. Key renewal is governed by inequality-based conditions on elapsed time (Δt ≤ 30 minutes) and encryption usage (n ≤ 10 operations), yielding a mathematically bounded key lifecycle without manual intervention or external infrastructure. System performance and operational security properties are evaluated in a simulated cloud environment using file sizes ranging from 100 KB to 10 MB. Quantitative metrics include encryption and decryption time complexity, computational overhead relative to AES-only encryption, key variability measured by Hamming distance, and data integrity verification using SHA-256. Experimental results demonstrate linear scalability and a stable average overhead of approximately 12.8%, indicating a bounded constant-factor cost independent of workload size. Successive AES-256 keys exhibit a mean Hamming distance of 127.42 bits, consistent with high key variability and effective key freshness. These findings show that analytically constrained key rotation enables controlled symmetric-key exposure while preserving practical efficiency overall.